Mechanical and corrosion properties of AlCu matrix hybrid composite materials - Islak Serkan (National Library of Serbia, 2019)
In this study, AlCu matrix hybride composites with various ratios of boron carbide (B4C), hexagonal boron nitride (hBN), and graphite (Gr) were produced by using hot-pressing method. The microstructure, density, mechanical and corrosion properties of these composites were investigated. Optical microscopy, scanning electron microscopy, and X-ray diffraction were used to characterize the microstructures, and the experimental densities of the composites were measured using a helium pycnometer. The mechanical properties including the hardness and transverse rupture strength were investigated using hardness and three-point bending tests, respectively. In addition, the hybrid composites were immersed in an aqueous solution of 3.5 wt.-percent NaCl at pH 3 for potentiodynamic and corrosion rate measurements. These tests revealed that a microstructure in which reinforcing particles are almost homogeneously dispersed in the matrix was obtained. Density measurements have shown that very dense and compact hybrid AMCs are produced. The hardness and transverse rupture strength of the composites were significantly increased by particulate addition to the matrix. Depending on the type and amount of reinforcement material, differences in the corrosion resistance of the hybrid composites have been determined. The results show that AlCu-8B4C-2Gr hybrid composite material has the highest corrosion resistance among the composite materials.
Keywords: corrosion; hybrid composite; Chemical technology; TP1-1185; mechanical properties; hot-press sintering